Research on Psychache in Suicidal Population: A Bibliometric and Visual Analysis of Papers Published During 1994–2020 - Cheng, Yin; Zhao, Wei-Wei; Chen, Shu-Yan; Zhang, Yan-Hong (Frontiers in Psychiatry, 2021)
Background: Psychache is a negative introspective experience, which is positively associated with the risk of suicide, independently of depression. It is undeniable that psychache is an important influencing factor to trigger suicide, which can also mediate the effect between depression and suicide variables. Nevertheless, the research tendency and current hotspots on psychache of suicide population have not been systematically investigated based on bibliometric analysis. Aim: To analyze research status, hotspots and frontiers of psychological pain in the field of suicidology, so as to provide reference for domestic clinical research. Methods: The literature related to psychache in suicide individuals published between 1994 to 2020 was included and selected from the Web of Science Core Collection database on May 28, 2021. CiteSpace (version 5.7.R2) software was used to visualize and analyze highly cited journals, authors and articles as well as co- occurrence analysis for countries, institution, authors and keywords. Results: A total of 230 articles from WoS database were included. The number of papers over the years showed an overall upward trend. The United States has made the largest contribution, with the majority of publications (89, 38.70%), followed by Canada (48, 20.87%), Israel (31, 13.48%), China (20, 8.80%) and Portugal (17, 7.39%). The most productive institution was Queen's University. Edwin S Shneidman has the largest achievement and profound influence, and the most prolific author is Holden RR. However, the cooperation between institutions and authors was comparatively weak. The current hotspots in this field focus on the studies on the relationships between depression, despair, psychache and suicide, the risk assessment of psychological pain and the development of psychological pain scales. Suicide and Life-Threatening Behavior was the most frequently cited journal in this field. Conclusions: This analysis not only reveals the current research trend and hotspots, but also provides some instructive suggestions on the development of psychache in the suicidology. Future work should pay more attention to develop effective psychological pain intervention programs for diverse suicide population. Additionally, longitudinal study can also be conducted to grasp the trajectory changes of psychological pain among suicide individuals.